Analisis Kualitas Pelayanan Administrasi Terpadu Di Kecamatan Plaju Kota Palembang - Hastuti, Ria; Hakim, Arif Rahman; Syuroh, Mat (@-Publik: Jurnal Administrasi Publik, 2025)
This study entitled "Analysis of Quality of Integrated Administrative Services in Plaju District, Palembang City". This study aims to determine the quality of integrated administrative services in Plaju District, Palembang City. The method used is qualitative with data collection techniques namely interviews, documentation, and observation. This study uses Zeithaml's theory regarding the service quality model. The results of this study indicate that 1) Tangibles, Buildings, Office rooms and facilities, Personnel and uniforms have been implemented properly. 2) Reliability, consisting of: Service competence and professionalism have been well implemented. 3) Responsiveness, accessibility or ease of getting services has been implemented properly. 4) Assurance, assurance that the problems faced by the community can be resolved or their needs can be fulfilled has not been implemented properly. 5) Empathy, attention or compassion for the interests/problems faced by the community, has been implemented properly. This problem was found from the results of analysis of document data, results of interviews with stakeholders and the public.